Axillary intranodal palisaded myofibroblastoma: report of a case associated with chronic mastitis. (16th October 2014) - D'Antonio, Antonio; Addesso, Maria; Amico, Paolo; Fragetta, Filippo
Abstract : Intranodal palisaded myofibroblastoma is a rare tumour of the lymph node that may be derived from myofibroblasts. The most usual area of presentation is the inguinal lymph nodes, but occurrence within other areas has also been reported. It is characterised by spindle cells, amianthoid-like fibres, and by the proliferation of hemosiderin-containing histiocytes in the lymph node. Although intranodal palisaded myofibroblastoma is benign, it is frequently confused with metastatic lesions, especially when it occurs in atypical sites. We herein report the second case of axillary intranodal palisaded myofibroblastoma occurring in a woman with a granulomatous chronic mastitis. The salient clinicopathological features of this unusual tumour are presented with emphasis to the pathogenesis of the tumour as well as to its histological and immunohistochemical characteristics. Clinicians and pathologists must be aware of this rare tumour to avoid a misdiagnosis of malignancy and assure patient a correct therapeutic management.